The Role of Helicobacter Pylori Bacterium in Cardiovascular Disease - Alazraqi, Adnan; Sahib, Ahmed; Dalal, Meinaa; Hanan, Zaman (Journal of Biomedicine and Biochemistry, 2023)
Introduction Atherosclerosis, ischemic heart disease, myocardial in- farction, and coronary artery disease are just a little of the cardiovascular anomalies that frame heart disease. It is the most important reason of death in any country on the globe. Heart disease has been associated to a number of general and new risk factors, counting infectious and noninfec- tious Infectious agents.Objective Understand The Role of Helicobacter pylori bacterium in cardiovascular diseaseResults and Discussion Accumulation levels indicated in this study were significantly higher in samples taken from Al-Hay brick factories than those taken from Al-Ahdeb oil fields, except for Lead (Pb), which was detected to be higher in samples of Al-Ahdeb oil fields. All concentration levels detected were high and considered hazardous to the health of organ- isms habituating within polluted areas since accumulation in tissues was reported to cause harmful negative effects on kidney function. Conclusion Accumulation levels indicated in this study were signifi- cantly higher in samples taken from Al-Hay brick factories than those taken from Al-Ahdeb oil fields. All concentration levels detected were high and considered hazardous to the health of organisms habituating within polluted areas.